Flood risk assessment and management how to specify hydrological loads, their consequences and uncertainties - Schumann, Andreas 1953-.; SpringerLink (Online service). (Berlin Heidelberg New York Springer, 2011)
This book examines many aspects of flood risk management in a comprehensive way. As risks depend on hazard and vulnerabilities, not only geophysical tools for flood forecasting and planning are presented, but also socio-economic problems of flood management are discussed. Starting with precipitation and meteorological tools to its forecasting, hydrological models are described in their applications for operational flood forecasts, considering model uncertainties and their interactions with hydraulic and groundwater models. With regard to flood risk planning, regionalization aspects and the options to utilize historic floods are discussed. New hydrological tools for flood risk assessments for dams and reservoirs are presented. Problems and options to quantify socio-economic risks and how to consider them in multi-criteria assessments of flood risk planning are discussed. This book contributes to the contemporary efforts to reduce flood risk at the European scale. Using many real-world examples, it is useful for scientists and practitioners at different levels and with different interests.
Preface -- 1. Hydrological aspects of risk management -- Uncertainties in weather forecast - reasons and handling -- 3. Interpolation of precipitation for flood modelling -- 4. Framing uncertainties in flood forecasting with ensembles -- 5. Design of artificial neural networks for flood forecasting -- 6. Advances in regionalising flood probabilities -- 7. Rainfall generators for application in flood studies -- 8. Copulas - New Risk Assessment Methodology for Dam Safety -- 9. Hydraulic Modelling -- 10. Groundwater the Subterranean Part of Flood Risk -- 11. Quantification of socio-economic flood risks -- 12. Application of scenarios and multi-criteria decision making tools in flood polder planning -- Index.
Electronic reproduction.
Keywords: Flood forecasting; Floods -- Risk assessment; Flood control; Electronic books